MEDIEVAL EXAMPLES IN FOREIGN SCIENTIFIC RESEARCH: FINDS AND PROSPECTS (Південний архів (історичні науки), 2025)
The aim of the article is to compare Foreign Studies of medieval examples, to assess the role of this type of narrative sources in the religious and cultural space of Western Europe of the XII–XV centuries. The methodological basis of the work is founded on the general scientific principles of historicism, objectivity, and systematicity, as well as specialized historical methods: the problem-historiographical and comparative-historical approaches. Scientific novelty. The study reveals the role of exemplorum in preaching practice, deepens the ideas of scientists regarding their modification, correlates assessments of these sources’ role in the religious and cultural space of Western Europe. A detailed comparison of the leading European historians’ approaches to the interpretation of exempli showed insufficient study of the indicated phenomenon. Special attention is paid to the specifics of the use of examples in sermons, the evolution of their form and content from Antiquity to the Middle Ages, as well as the role of this type of historical sources in the formation of ideas, value orientations and the cultural space of medieval Western Europe. The analysis of the works of Jacques Le Goff, Boris Geremek, Marie-Anne Polo de Beaulieu, Jacques Berlioz, Thomas Crane and other authors allowed us to compare the approaches of leading medievalists to the interpretation of exemplorum as a historical source or (and) literary work, to systematize the ideas of scientists about their content and from evolution, and the role in the religious and cultural life of the XII–XV centuries. The article formulates prospects for further research of this type of historical sources. Conclusions. Exempla played a key role in the religious and cultural life of Western Europe during the High Middle Ages. In the XII–XIV centuries, they became an essential means of perception of the population's Christian values. Exempla in the XV–XVI centuries gradually lost their preaching function and were transformed into secular works. Further study of these historical sources will allow us to explore more deeply the cultural and religious life in European Society during the Middle Ages.
Keywords: homiletic “examples”, Latin-language historical sources, High Middle Ages, Western European historiography